Patriotism and national identity in Uzbek female students abroad - Rahmanova, Gulchehra; Davlatova, Khulkaroy; Egamberdiyeva, Nodira; Khusanova, Khayriniso; Abduvaliyev, Makhamatjon; Maksudova, Holiskhon (Edelweiss Applied Science and Technology, 2025)
In an increasingly globalized world, the tension between global citizenship and national identity has garnered significant academic interest. For Uzbek female students studying abroad, the intersection of national identity and international education presents unique challenges and opportunities. This study explores how participation in international programs influences the national identity and patriotic sentiments of these students, who are often seen as cultural custodians within Uzbek society. Drawing on theories of cultural identity, globalization, and educational sociology, this research examines how Uzbek female students navigate their sense of patriotism while engaging with diverse cultural environments abroad. Through a mixed-methods approach involving surveys and interviews, the study reveals that, despite challenges of cultural dislocation and identity negotiation, most students retain a strong connection to their homeland, with a clear intention to return and contribute to Uzbekistan’s development. The findings highlight the dual role of social media as both a bridge to home and a source of global perspectives, shaping students' perceptions of national and global identities. The study concludes with policy recommendations for educational institutions and policymakers to foster environments that strengthen national identity and promote a sense of responsibility toward Uzbekistan, ensuring that international education supports the cultivation of globally aware yet culturally rooted future leaders. Additionally, recommendations are given to Uzbek female students studying abroad to help them maintain their cultural identity, adapt effectively to new environments, and leverage their international experiences for the benefit of Uzbekistan upon their return.